PENGARUH PEMBERDAYAAN DAN KOMPETENSI TERHADAP KINERJA MELALUI MOTIVASI DAN KOMITMEN ORGANISASIONAL PADA PEGAWAI PEMERINTAH KABUPATEN BATANG (Studi pada Badan di Lingkungan Kantor Bupati Batang) - Adhi Bhaskoro, 12.5202.0150; Abdul Rozak, Hasan (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to analyze and describe the influence of empowerment and competence against the performance mediated Motivation and Organizational Commitment in Batang Government. Population and sample of the study is Civil Servant at Bodies in the Trunk Regent Office. This study is a census of the number of respondents 127 people. The data were obtained by distributing questionnaires as many as 127 pieces. Techniques of analysis in this study included a test instrument consisting of validity and reliability testing, further testing of the model with regression analysis, F test, Coefficient of Determination Test, then test hypotheses through Partial Test (t) and the Test of Mediation. The results of this study stated that: (1) Empowerment significant negative effect on motivation, (2) Empowerment positive and significant impact on Organizational Commitment, (3) Competence positive and significant effect on motivation, (4) does not affect the competence of Organizational Commitment, (5) Empowerment and significant positive effect on performance, (6) Competence positive and significant effect on performance, (7) Motivation no effect on performance, (8) Organizational commitment has no effect on performance, and (9) The direct influence of empowerment and competence towards more effective performance than the Motivation and Commitment mediated by Organisional. Key Words: Empowerment, Competence, Motivation, Organizational Commitment, Performance